Hydrothermal conditions dominated sensitivity and lag effect of grassland productivity in Yunnan Province, China: Implications for climate change - Yan Fang; Long Wan; Jing Tong; Guijing Li; Jing Pang; Enfu Chang; Linglan Chen; Zixuan Shi (Agricultural Water Management)
Net primary productivity (NPP) is an important indicator of carbon and water cycles in grassland ecosystems and is highly sensitive to climate change. This study focused on grassland and its sub-regions in Yunnan Province and analyzed the productivity of grassland ecosystems under different hydrothermal conditions from 2001 to 2021. The results indicated that grassland experienced a warming and drying trend, with an overall upward trend averaging 5.30 gC·m−2·a−1. Notably, the central Yunnan Plateau region boasted the highest productivity growth rate, reaching 7.67 gC·m−2·a−1. The response of grassland productivity to climate change under different hydrothermal conditions exhibited distinct spatial heterogeneity and complexity. Grasslands in the hot and humid zone of southwestern Yunnan presented the highest sensitivity to changes in precipitation, temperature, and solar radiation, at 3.08 (gC·m−2·a−1)/mm, 53.3 (gC·m−2·a−1)/°C, and 4.07 (gC·m−2·a−1)/(MJ·m−2), respectively. In the Qinghai-Tibetan Plateau alpine region, rising temperatures contributed to productivity growth. In contrast, warmer temperatures and water stress led to a decline in grassland productivity in the hot and dry vally of the Jinsha River. In addition, grassland productivity showed variable lag effects in different hydrothermal regions. The areas where grassland productivity with a 3-month lag effects in response to temperature, precipitation, and solar radiation accounted for 25.26 %, 34.52 %, and 16.04 % of the region, respectively. The grassland productivity responses to temperature and precipitation exhibited a long lag effect, primarily observed in dry and hot areas. This study is crucial for guiding adaptive vegetation management in Yunnan grassland ecosystems under different hydrothermal conditions to better cope with climate change.